The efficiency and productivity of Indian pharmaceutical companies : a firm-level analysis - Mohammad, Aas. (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2019)
This book evaluates the performance of the Indian pharmaceutical industry, which plays an important role in economic development. It highlights the role the government has had in facilitating the growth of the industry from non-existence, before the 1970s, to being one of the largest pharmaceutical industries in the world today. The text employs various useful techniques to provide an understanding of productivity and efficiency, such as data envelopment analysis, stochastic frontier analysis, the Malmquist Productivity Index and the Hicks-Moorsteen Productivity Index. --
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Pharmaceutical industry -- India; Industria farmacéutica -- India; Libros electrónicos.